(untitled) (Revista Escenarios Sociojurídicos, 2023)
The objective of this project is to analyze the right to cultural integrity as seen from the artisan sector in Colombia during the Covid-19 pandemic. For this, a mixed model was used to cover two fields of the academy, the first was developed from the interpretation of a bibliographic record that contemplates various plans that Colombia has for the determination of the cultural integrity of artisans in the country, the second was an interview in which the perspective that artisans have on the issue in question is contemplated.